Moral value of Nobita in subtitle of Stand By Me Doraemon 2 - Denisa Puspa Cahya; Irwan Efendi (Mitra Palupi, 2022)
Background: Film acts as a new tool used to spread entertainment that has become a habit in the past and presents stories, events, music, drama, comedy and other technical offerings to the general public. Subtitling is a translation of film dialogue written at the bottom of a film. In other words, subtitles are in the form of text. And the purpose of translating the film or subtitle is to help viewers enjoy the storyline of the film they are watching. Purpose: This study aims to determine the moral values ​​of Nobita's character in the film Stand By Me Doraemon 2 through film subtitles. Design and methods: In this study, researchers used a qualitative approach with a qualitative descriptive research design and data collection techniques in this study used content analysis by analyzing the subtitles in the film Stan by Me Doraemon 2. Results: The results of the study, it was found that several characters in Nobita's character were: careless, not honest, lazy, loving, spoiled, crybaby, grumpy, passionate, outspoken, confident and brave. Of the existing characters, only a few characters are exemplary in everyday life, especially for elementary school students, such as compassionate, enthusiastic and brave.